In vivo regulation of the Escherichia coli araC promoter. - Hahn, S (1983)
The ara pC promoter is known to be derepressed about fivefold for 20 to 30 min after the addition of arabinose. This transient derepression was studied by using araC::Mu lac insertions and araC-lacZ gene fusions. In strains containing increased levels of araC protein, the pC promoter became progressively less derepressible, but the ara pBAD promoter remained normally inducible. Repression of pC was reestablished 20 min after induction in araB mutants, but did not occur in arabinose-transport-deficient mutants. Finally, mutant araCc proteins which normally do not repress pC did so in the presence of arabinose.